Теоретические модели функционирования и обеспечения механической надежности культиваторов с подпружиненными рабочими органами - Гринченко, А. С.; Алферов, А. И.; Grynchenko, Oleksandr; Alferov, Olexsyi; Алфьоров, О.І.; Гринченко, О.С. (КНТУ, 2015)
Предложена модель автоколебаний, как основу динамической теории расчета обработки почвы вибрационными рабочими органами и приведена методика обеспечения их безотказности. Запропоновано модель автоколивань, як основу динамічної теорії розрахунку обробки ґрунту вібраційними робочими органами і наведено методику забезпечення їх безвідмовності. The process is compulsory cultivation operation at tillage. Considering the work of the working bodies of elastic cultivators only to ensure mechanical reliability and excluding dynamic components come to demand increase stiffness and eliminating vibrations working bodies. The present approach allowed to identify the impact speed of the unit, the natural frequency fluctuations in the relative movement and speed of the paw point of attachment to the rack. Introduced factor dynamics loosening. Laid down in Article theoretical basis of dynamic characterization loosening can reasonably do for maintaining reliability. Dynamic characteristics of workers should be determined based on the model oscillation, it can reasonably predict the mechanical reliability.
Теоретичні моделі функціонування та забезпечення механічної надійності культиваторів з пружними робочими органами
Theoretical models of functioning and providing technical reliability cultivators with elastic working bodies
Keywords: динамический расчет; безотказность; обработка почв; динамічний розрахунок; безвідмовність; обробка грунту; dynamic calculation; reliability; tillage